Oral Biofilms from Symbiotic to Pathogenic Interactions and Associated Disease –Connection of Periodontitis and Rheumatic Arthritis by Peptidylarginine Deiminase - Kriebel, Katja; Hieke, Cathleen; Müller-Hilke, Brigitte; Nakata, Masanobu; Kreikemeyer, Bernd (Frontiers in Microbiology, 2018)
A wide range of bacterial species are harbored in the oral cavity, with the resulting complex network of interactions between the microbiome and host contributing to physiological as well as pathological conditions at both local and systemic levels. Bacterial communities inhabit the oral cavity as primary niches in a symbiotic manner and form dental biofilm in a stepwise process. However, excessive formation of biofilm in combination with a corresponding deregulated immune response leads to intra-oral diseases, such as dental caries, gingivitis, and periodontitis. Moreover, oral commensal bacteria, which are classified as so-called “pathobionts” according to a now widely accepted terminology, were recently shown to be present in extra-oral lesions with distinct bacterial species found to be involved in the onset of various pathophysiological conditions, including cancer, atherosclerosis, chronic infective endocarditis, and rheumatoid arthritis. The present review focuses on oral pathobionts as commensal and healthy members of oral biofilms that can turn into initiators of disease. We will shed light on the processes involved in dental biofilm formation and also provide an overview of the interactions of P. gingivalis, as one of the most prominent oral pathobionts, with host cells, including epithelial cells, phagocytes, and dental stem cells present in dental tissues. Notably, a previously unknown interaction of P. gingivalis bacteria with human stem cells that has impact on human immune response is discussed. In addition to this very specific interaction, the present review summarizes current knowledge regarding the immunomodulatory effect of P. gingivalis and other oral pathobionts, members of the oral microbiome, that pave the way for systemic and chronic diseases, thereby showing a link between periodontitis and rheumatoid arthritis.